Effects of density, species interactions, and environmental stochasticity on the dynamics of British bird communities. Issue 8 (19th June 2022) - Sandal, Lisa; Grøtan, Vidar; Sæther, Bernt‐Erik; Freckleton, Robert P.; Noble, David G.; Ovaskainen, Otso
Abstract: Our knowledge of the factors affecting species abundances is mainly based on time‐series analyses of a few well‐studied species at single or few localities, but we know little about whether results from such analyses can be extrapolated to the community level. We apply a joint species distribution model to long‐term time‐series data on British bird communities to examine the relative contribution of intra‐ and interspecific density dependence at different spatial scales, as well as the influence of environmental stochasticity, to spatiotemporal interspecific variation in abundance. Intraspecific density dependence has the major structuring effect on these bird communities. In addition, environmental fluctuations affect spatiotemporal differences in abundance. In contrast, species interactions had a minor impact on variation in abundance. Thus, important drivers of single‐species dynamics are also strongly affecting dynamics of communities in time and space.